"Contrôle Automatisé d'une Usine de Poulets avec l'API Zelio" - احمد, بن عمر; كمال, سخري; اسماعيل, حريز بلقاسم (University of El-Oued, 2021)
The main objective of this study is to establish a program to facilitate and control broiler farms in an automated manner and to compensate for primitive breeding in order to improve the product. Where we developed a program to become control of the temperature and lighting ... etc without human intervention الهدف الرئيسي من هذه الدراسة هو عمل برنامج لتسهيل و التحكم في مزارع تربية الدجاج اللاحم بشكل آلي للتعويض عن التربية البدائية من أجل تحسين المنتوج. حيث قمنا بتطوير البرنامج ليصبح التحكم في درجة الحرارة و الإنارة ...الخ دون تدخل الإنسان
مذكرة ماستر تخصص commande electrique
Keywords: key words : program , control , automated; كلمات مفتاحية : برنامج , تحكم , الي